Mortality and morbidity from malaria among children in a rural area of The Gambia, West Africa. - Greenwood, B; Bradley, A; Greenwood, A; Byass, P; Jammeh, K; Marsh, K; Tulloch, S; Oldfield, F; Hayes, R (1987)
Mortality and morbidity from malaria were measured among 3000 children under the age of 7 years in a rural area of The Gambia, West Africa. Using a post-mortem questionnaire technique, malaria was identified as the probable cause of 4% of infant deaths and of 25% of deaths in children aged 1 to 4 years. The malaria mortality rate was 6.3 per 1000 per year in infants and 10.7 per 1000 per year in children aged 1 to 4 years. Morbidity surveys suggested that children under the age of 7 years experienced about one clinical episode of malaria per year. Calculation of attributable fractions showed that malaria may be responsible for about 40% of episodes of fever in children. Although the overall level of parasitaemia showed little seasonal variation, the clinical impact of malaria was highly seasonal; all malaria deaths and a high proportion of febrile episodes were recorded during a limited period at the end of the rainy season.